Review on the book «The Oxford History of Anglicanism» (Oxford, 2017) - Anastasia Andreyevna Palamarchuk (Религия, церковь, общество, 2018)
The reviewed volume «The Oxford History of Anglicanism. Vol. 1. Reformation and Identity, с. 1520–1662 » (Ed. by A. Milton. Oxford, 2017) definitely is a seminal work on English ecclesiastical history. The concept of the Church of England as a «contested identity» and Anglicanism as a global cultural-historical phenomenon open a new perspective for the historians of the Church of England.